Impact of Agile Project-Based Learning: A Case Study of a PWM Inverter in Engineering Education - Wanapri Pangaribuan; Bakti Dwi Waluyo; Selly Annisa Binti Zulkarnain (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the impact of integrating APBL with a PWM-controlled three-phase inverter project in vocational engineering education. This study was conducted across six vocational high schools in Indonesia and adopted a quasi-experimental, mixed-methods approach involving 223 students from the Industrial Electronics Engineering programs. The intervention was structured into sprint cycles, following APBL principles, which emphasized collaboration, iterative problem-solving, and hands-on experience. Data were collected through pre- and post-tests, student perception questionnaires, activity observations, product assessments, and semi-structured interviews. Results show a significant improvement in students’ technical competencies, with average pretest and posttest scores rising from 59.2 to 83.7 and a mean N-Gain of 0.60, classified as moderate. The paired-sample t-test indicated a large effect size (Cohen’s d = 2.03, p < 0.001). Students reported positive perceptions of motivation, teamwork, and problem-solving skills, supported by high mean activity observation and project assessment rubrics scores. The qualitative findings from the interviews highlighted enhanced engagement, collaboration, and autonomy. The study concludes that APBL is highly effective in bridging the gap between theory and practice in power electronics education when combined with technology-enhanced learning media. Recommendations for broader adoption and future research into long-term and scalable implementations of APBL in diverse educational contexts are provided.